Peningkatan Kemampuan Peserta Didik Kelas IV SD Negeri 2 Wates Kulon Progo Semester I Tahun Pelajaran 2018/2019 dalam Menyebutkan Nama dan Tugas Malaikat Allah Menggunaan Metode Smart Games - fatkiyah01 fatkiyah (Islamic University of Indonesia, 2019)
AbstractThe success of the teaching and learning process in the classroom is determined by the learning strategy. Without being implemented through the right strategy, the components of teaching and learning process will not have meaning in achieving goals. Therefore, each teacher will be required to implement certain strategies or methods in the implementation of learning. The aim of this study is to improve thinking skills of the student achievement after the implementation of learning strategies. This research uses action research as much as three rounds. Each round consists of four stages: design, activity and observation, reflection, and refinement. The targets of this study were grade IV students. The data obtained were in the form of test results, observational sheets of teaching and learning activities. From the results of the analyst found that student achievement has increased from cycle I to cycle III namely, cycle I (68.00%), cycle II (80.00%), cycle III (92.00%). The conclusion of this research is the smart games method and the make a match type of cooperative learning can have a positive effect on student learning motivation, and this learning model can be used as an alternative to PAI learning. Keywords: Smart Games, Increasing Student Ability, Names and Duties of Angels of Allah